Continuous and noninvasive measurement of systolic and diastolic blood pressure by one mathematical model with the same model parameters and two separate pulse wave velocities - Chen, Yan (2013)
There is keen interest in continuous and noninvasive blood pressure (BP) measurement. However, many technologies have a shortcoming of complex mechanical structure. In our study, two arterial pulses are acquired by photoplethysmography (PPG) at ear and toe in order to explore a new method of measuring BP by pulse wave velocity (PWV). We previously validated and reported a BP-PWV mathematical model with measurements from humans with no evidence of cardiovascular disease, but were only able to determine PWV related to diastolic blood pressure (DBP). In this paper, we propose methods of identifying pulse transmit time (PTT) in low, normal and high systolic blood pressure (SBP) conditions. By averaging the PTT’s of incident wave and reflected wave for non-systematic error reduction, we obtain a PWV that is suitable for estimating SBP. SBP and DBP are estimated by two separate PWV’s based on the previously calibrated models. Experimental measurements are conducted on 26 subjects (age 19 ± 1 and 60 ± 1) with no evidence of cardiovascular disease. The measurement errors (Mean Deviation = 2.16 mmHg (SBP) and 1.49 mmHg (DBP); Standard Deviation = 6.23 mmHg (SBP) and 6.51 mmHg (DBP)) satisfy the accuracy criteria of Association for the Advancement of Medical Instrumentation. The results verify that SBP and DBP can be estimated by one mathematical model with the same model parameters and two separate PWV’s.